Gettysburg Address: and, Bunker Hill oration - Lincoln, Abraham (Orville Brewer Pub. Co., 1920)
Gettysburg Address -- The Bunker Hill oration: an address delivered at the laying of the corner stone of the Bunker Hill Monument at Charleston, Mass., on the 17th of June, 1825.